A study on organizational engagement in Corporate Social Responsibility (CSR) programs / Noor Anis Hussain and Noor Rasyiqah Shaharuddin - Hussain, Noor Anis; Shaharuddin, Noor Rasyiqah (2018)
Corporate Social Responsibility (CSR) are growing and every organization want to involve in CSR as they know that they cannot focus on their business solely and neglect the social responsibility for the community. There are many reason on why organization wants to participate in CSR activities and this study seek to examine what is the factor that contribute organizations in Sungai Petani which are from three industries namely manufacturing, hotel, and developers to involve in CSR. The three factors that has been examined is financial return, firm size, and corporate reputation. Therefore, a purposive sampling has been used and questionnaire has been distributed for 113 organizations that the researchers believed they involved in CSR activities. From 113, the returnquestionnaires that have been answered is 63. From the data analysis, the researchers found that the most dominant factor that influenced organizational engagement in CSR is corporate reputation. This shows that most of the organizations from the three industries that has been mentioned engage themselves in CSR to ensure that their corporate image is good and maintain as an organization that has a good reputation.